Lifestyle behaviour and prevalence of cardiovascular risk factors : a pilot study comparing comparison between Kiribati and European seafarers - Robert von Katzler and Birgit-Christiane Zyriax and Bettina Jagemann and Joachim Westenhöfer and Hans-Joachim Jensen and Volker Harth and Marcus Oldenburg (BMC public health, 2019)
Background